PENGARUH CAPITAL ADEQUACY RATIO, FINANCING TO DEPOSIT RATIO DAN NON PERFORMING FINANCINGTERHADAP RETURNON ASSET PADA PT BANK MUAMALATINDONESIA, Tbk - Luthfi Alfiyah; Wahyuningsih Wahyuningsih; Marti Dewi Ungkari (Jurnal Ekonomi Dan Bisnis, 2016)
The title of this research is: “The Influence of Capital Adequacy Ratio, Financing to DepositRatio, and Non Performing Financing to Return on Asset at PT Bank Muamalat Indonesia, Tbk”. Thisresearch aimed to know the influence of Capital Adequacy Ratio, Financing to Deposit Ratio, and NonPerforming Financing to Return on Asset. The method used in this research is descriptive method ofanalysis and verification method. Data collection techniques using literatureresearch (library research)and documentation research. Analysis of the data used is the classical assumption test first formmultikolonieritas test, autocorrelation test, heteroscedasticity test and test for normality.Furthermore, using multiple linear regression statistical test, the coefficient of determination andtesting through the F test and t test using SPSS version 20 statistical application for Windows.  Theresearch findings show that Capital Adequacy Ratio, Financing to Deposit Ratio, and Non PerformingFinancing simultaneously or partially no significant influence to Return on Asset. Keyword: Capital Adequacy Ratio, Financing to Deposit Ratio, Non Performing Financing, and Return on Asset.